Karakteristik Kualitas Cuka Aren (Arenga pinnata Merr) Tradisional Aceh Berdasarkan SNI 01-4371-1996 - Masyitah Masyitah (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2025)
Palm sap (Arenga pinnata Merr) as the main ingredient in traditional vinegar production. The result of the fermentation process of palm in the form of vinegar.This study aims to determine the quality of traditional palm vinegar (Arenga pinnata) typical of Aceh based on SNI 01-4371-1996. The type of research includes descriptive analysis. Testing the quality of palm vinegar include acetic acid content, Nacl, alcohol content, test total sugar, the amount of dissolved solids, contaminant of metal (Pb, Cu, Zn), arsenic contamination, microbial contamination and pH. The results showed that the standart that meet on vinegar are the liquid form and acid odor, residue of alcohol 3,54%, contaminant of metal Pb and Cu 0,20 mg/kg and 0,31 mg/kg, microbial contamination 1×10-1, and not detection of arsenic contaminant. pH test 3,27. Standart that not meet are the total acetic acid content 0,18%, Nacl 0,06, the amount of dissolved solids 5,2 °Brix and contaminant of metals Zinc (Zn) 2,76 mg/kg.